Peningkatan Gerak Lokomotor dengan Penerapan Permainan Tradisional Berbasis Literasi Numerasi pada Siswa SD Kelas Bawah - Ramadhani, Bintang Tri; Pamungkas, Hari; Niddomudin, Muhammad; Agyanur, Shoffurijal; Husen, Ashari (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Physical education and sports have also been linked to the social, academic, and behavioral benefits, as well as the movement of elementary school children, but not all of these aspects run properly, especially in motor movements in children. And it is evidenced in the initial observation that children's locomotor movements tend to be lacking. This study aims to improve locomotor movements with the application of traditional games based on numeracy literacy in lower grade elementary school students. This study uses the Classroom Action Research (PTK) model, consisting of planning, acting, observing, and reflection. The study consisted of 44 students from class III of SDN Bambang. Furthermore, data collection used observation sheets and conducted pre-cycle observations with the aim of 85% of students in the > sufficient category. The results showed an increase in students' locomotor movements where 56.8% (25 students) had entered the sufficient-good category, while there were still 43.2% (19 students) still in the insufficient category. And in Cycle II, students' locomotor movements were in the > sufficient category with a percentage of 86.4% (38 students). The conclusion of this study is that there is an increase in locomotor movements with the application of traditional games based on numeracy literacy in lower grade students of SDN 02 Bambang.